Predictors of Condom-use among Young Never-married Males in Nigeria (Journal of Health, Population and Nutrition, 2011)
This study examined the factors that influence condom-use among young never-married males in Nigeria. Such information can help improve the design of a prevention programme for young never-married, especially, males to reduce their vulnerability to sexually transmitted infections (STIs) and HIV/AIDS transmission. Data were derived from the 2003 Nigeria Demographic and Health Survey (NDHS). Analysis of data was restricted to 827 males aged 15-24 years, who had never married or lived together with a woman. Both descriptive and analytical methods were used for assessing the net effects of socioeconomic factors on condom-use. The analysis used logistic regression models for determining the predictors of sexual behaviour and condom-use among young never-married males in Nigeria. About 43% of the study population was sexually experienced, and the use of a condom remained low. One in five reported the use of a condom at sexual debut. Level of education, place of residence in childhood, urban/rural region, religious affiliation, economic status index, and exposure to mass media were associated with sexual experience and use of protective measures. Economic status index and mass-media exposure were associated with the use of a condom by the respondents during their last sex encounter. About two-fifths (43%) of the young unmarried Nigerian men were sexually experienced but the condom-use remained low, thus making this sub-group of Nigerian population highly vulnerable to STIs, including HIV/AIDS. Key words: Acquired immunodeficiency syndrome; Condom-use; HIV; Sex behaviour; Sexually transmitted infections; Youth; Nigeria DOI: http://dx.doi.org/10.3329/jhpn.v29i3.7875 J HEALTH POPUL NUTR 2011 Jun;29(3):273-285